Changes of Metabolic Disorders Associated Peripheral Cytokine/Adipokine Traffic in Non‐Obese Chronic Back Patients Responsive to Burst Spinal Cord Stimulation. Issue 1 (24th October 2017) - Muhammad, Sajjad; Chaudhry, Shafqat R.; Yearwood, Thomas L.; Krauss, Joachim K.; Kinfe, Thomas M.
Abstract : Objectives: In our previous study, anti‐inflammatory IL‐10 serum levels were significantly elevated after burst spinal cord stimulation (SCS) in back pain patients and correlated with pain intensity. This current study extended cytokine analysis including metabolic‐associated adipokine/cytokine serum assessment in chronic back pain patients with co‐existing metabolic disorders such as diabetes, hypertension, and cardiovascular diseases. Methods: At baseline and after three months of burst SCS treatment, leptin (LP), adiponectin (AN), and ghrelin (GH) were recorded in non‐/pre‐obese chronic back pain patients with co‐existing metabolic disorders and compared to age‐/gender‐matched healthy controls (HC). Results: Mean BMI was 22 ± 0.81 kg/m 2 in 12 (five male/seven female) participants with diabetes in 6/12 (50%), hypertension in 9 (75%), and CVD in five patients (42%). Pre‐ and post‐SCS LP levels were significantly higher compared to healthy controls: pre‐SCS, 30567 (12, 996–58, 821) vs. HC, 7952 (4932–12, 583) pg/mL, p = 0.029; post‐SCS, 18, 890 (7140–44, 719) vs. HC, 7952 (4932–12, 583) pg/mL, p = 0.035. Pre‐ and post‐SCS changes of GH ( p = 0.18) and AN ( p = 0.8) did not differ significantly. GH serum levels correlated with AN (Spearman r = 0.5; p = 0.012; 95 CI 0.11 to −0.76) and AN levels were significantly correlated with higher age (Pearson correlation r = 0.8; p = 0.002; 95 CI 0.41–0.94) at baseline. Conclusions: This study determined serum changes of metabolic‐associated cytokines/adipokines in non‐obese chronic back pain patients responsive to burst SCS suggesting that neuroinflammation assessment may consider pain‐associated mood, cognition, sleep, and metabolic state.